Fiber membrane as well as preparation method and application thereof
By designing a fiber membrane with polysaccharide layer structure and using electrospinning and glutaraldehyde cross-linking technology, the existing nanofiber membranes have been solved, with few types, fast degradation speed and poor antibacterial effects, and a significant improvement in the periodontal tissue repair effect has been achieved.
Patent Information
- Application Number
- CN202411883435.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
There are fewer types of nanofiber membranes used to promote periodontal tissue repair, and their degradation speed is fast and their antibacterial effect is poor, resulting in unsatisfactory periodontal repair effect.
A fiber membrane consisting of polysaccharide layer 1 and polysaccharide layer 2 is provided. The pores of polysaccharide layer 1 are larger than polysaccharide layer 2. The film is spun into a film by electrospinning technology and cured by cross-linking of glutaraldehyde to form a fiber membrane with slow degradation speed and local antibacterial effect.
The fiber membrane has slow degradation rate, significant antibacterial effect, significantly improved periodontal repair effect, simple preparation method and easy to obtain raw materials.
Smart Images

Figure CN119680013A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fiber membrane, a preparation method and application thereof. Background Art
[0002] The periodontium is composed of the gingiva, periodontal ligament, cementum, and alveolar bone and is a hierarchical tissue whose primary function is to provide physical and mechanical support to the teeth. Severe periodontitis, an inflammatory disease triggered by oral bacterial biofilm, can lead to severe destruction of the soft and hard tissues of the periodontium and result in impaired tooth function and aesthetics. Although current treatments can limit the progression of the disease by controlling the inflammatory aspects, complete periodontal regeneration is difficult to achieve.
[0003] The ultimate goal of periodontal therapy is to regenerate lost periodontal tissues, including functional reattachment of the periodontal ligament to newly formed cementum and alveolar bone. This requires a highly coordinated spatiotemporal healing response, including cementum formation with the concomitant reattachment of periodontal ligament fibers to previously contaminated root surfaces, and bone formation within the periodontal defect. In addition to the challenges posed by the complex architecture of the periodontium, healing is further complicated by the avascularity of the tooth surface, which means that healing of all periodontal wounds is secondary. Furthermore, healing is also impaired by the presence of oral bacteria on non-implant surfaces, which can negatively impact the wound healing process following periodontal therapy.
[0004] Guided bone membrane (GTR) has become the standard surgical treatment for periodontal regeneration; however, despite histologically verified regeneration and positive results in selected clinical scenarios, the clinical effects of this technology still have significant variability. In fact, GTR remains unpredictable, and clinical results vary depending on the nature of the periodontal defect and the skills and experience of the surgeon. It is clear that periodontal regeneration has unique challenges. From a biological point of view, there should be a synergistic relationship between material degradation time and healing efficiency during periodontal tissue repair. In addition, competition between cell tissues also needs to be considered. Periodontal fibroblasts may fill the defect site first, causing osteoblast-related cells to be unable to function, resulting in failed periodontal regeneration. It is even more important to note that the oral flora will threaten the repaired cells. Although systemic antibacterial treatment is necessary in clinical practice, this undoubtedly increases the risk of side effects. Summary of the invention
[0005] The technical problem to be solved by the present invention is that there are few types of existing nanofiber membranes for promoting periodontal tissue repair. To this end, the present invention provides a fiber membrane, a preparation method and application thereof, which has a slow degradation rate, local antibacterial effect, and better periodontal repair effect.
[0006] The present invention provides a fiber membrane, which includes a polysaccharide layer one and a polysaccharide layer two, wherein the polysaccharide layer one and the polysaccharide layer two are bonded together, the material of the polysaccharide layer one is a cross-linked polysaccharide, the material of the polysaccharide layer two is a cross-linked polysaccharide, and the pores of the polysaccharide layer one are larger than the pores of the polysaccharide layer two.
[0007] In a certain embodiment, some features are described below and the remaining features are as described in the previous embodiment (hereinafter referred to as "in a certain embodiment").
[0008] In a certain embodiment, the fiber membrane is a fiber membrane used as an antibacterial material and / or a bone tissue repair material, for example, a fiber membrane used as a periodontal defect repair material.
[0009] In one embodiment, the fiber membrane has an area of 0.5×0.5 m2.
[0010] In one embodiment, the fiber membrane has a thickness of 200±25 μm.
[0011] In a certain embodiment, the fiber membrane consists of a first polysaccharide layer and a second polysaccharide layer.
[0012] In a certain embodiment, the number of the polysaccharide layer one is one.
[0013] In a certain embodiment, the number of the second polysaccharide layer is one.
[0014] In one embodiment, the pore size of the polysaccharide layer is 80 + 23μm.
[0015] In one embodiment, the porosity of the second polysaccharide layer is 10% to 14%, for example 12%.
[0016] In one embodiment, in the polysaccharide layer, the cross-linking is performed by glutaraldehyde cross-linking.
[0017] In one embodiment, in the polysaccharide layer 2, the cross-linking is performed by glutaraldehyde cross-linking.
[0018] In one embodiment, in the polysaccharide layer, the polysaccharide is one of chitosan, cellulose, starch, alginate and dextran, such as chitosan, and for example 50 kDa chitosan.
[0019] In one embodiment, in the second polysaccharide layer, the polysaccharide is one of chitosan, cellulose, starch, alginate and dextran, such as chitosan, and for example 50 kDa chitosan.
[0020] In one embodiment, the fiber membrane has an area of 0.5×0.5㎡;
[0021] The fiber membrane thickness is 200±25 μm;
[0022] The fiber membrane consists of a first polysaccharide layer and a second polysaccharide layer;
[0023] The first polysaccharide layer is attached to the second polysaccharide layer;
[0024] The material of the polysaccharide layer 1 is cross-linked polysaccharide;
[0025] The material of the polysaccharide layer 2 is cross-linked polysaccharide;
[0026] The number of layers of the polysaccharide layer 1 is 1;
[0027] The number of layers of the polysaccharide layer 2 is 1;
[0028] The pore size of the polysaccharide layer is 80 + 23 μm;
[0029] The porosity of the polysaccharide layer 2 is 12%;
[0030] The cross-linking is carried out through glutaraldehyde cross-linking;
[0031] In the first polysaccharide layer, the polysaccharide is 50 kDa chitosan;
[0032] In the second polysaccharide layer, the polysaccharide is 50 kDa chitosan;
[0033] The fiber membrane is a fiber membrane used as a periodontal defect repair material.
[0034] The present invention also provides a method for preparing a fiber membrane, which comprises the following steps:
[0035] (1) electrospinning a polysaccharide solution to obtain an electrospun membrane; the polysaccharide solution comprises polysaccharide and an organic solvent; and salt is added during the electrospinning process;
[0036] (2) Based on the electrospun membrane 1, electrospinning a polysaccharide solution to obtain a composite electrospun membrane; the polysaccharide solution is composed of polysaccharide and an organic solvent; and no salt is added during the electrospinning;
[0037] (3) Cross-linking the composite electrospun membrane obtained in step (2) with glutaraldehyde in water, washing, and drying to obtain a fiber membrane.
[0038] In a certain embodiment, the fiber membrane is the fiber membrane mentioned above.
[0039] In one embodiment, in step (1), the manufacturer of the instrument used for electrospinning is Shenzhen Tongli Micro-Nano.
[0040] In a certain embodiment, the polysaccharide is one of chitosan, cellulose, starch, alginate and dextran, such as chitosan, and for example 50 kDa chitosan.
[0041] In one embodiment, the organic solvent is a volatile electrospinning solution.
[0042] In one embodiment, the organic solvent is one of methanol, hexafluoroisopropanol, acetone, trifluoroacetic anhydride and water, such as trifluoroacetic anhydride.
[0043] In one embodiment, the concentration of the polysaccharide solution is 3.0-8.0 wt.%, for example, 5 wt.%.
[0044] In one embodiment, the electrospinning speed is 0.5-1 mL / h, for example 1 mL / h; mL refers to the volume of the polysaccharide solution.
[0045] In a certain embodiment, the negative voltage of the electrospinning is -3 kV; the positive voltage of the electrospinning is 15-20 kV, for example, 20 kV.
[0046] In one embodiment, the electrospinning time in step (1) is the same as the electrospinning time in step (2).
[0047] In one embodiment, in step (1), the electrospinning time is 4-6 hours, for example, 5 hours; in step (2), the electrospinning time is 4-6 hours, for example, 5 hours.
[0048] In one embodiment, the salt is sodium chloride, potassium chloride, copper sulfate, sodium bicarbonate and calcium chloride, such as sodium chloride; the average particle size of the salt is 1-10 μm, such as 5 μm (ie 5000 nm).
[0049] In one embodiment, the salt is added at a rate of 50 mg / min.
[0050] In a certain embodiment, the rotation speed of the electrospinning support roller should be controlled at 200-2000 r / min, such as 500-8000 r / min, and for example 600 r / min.
[0051] In one embodiment, the composite electrospun membrane has two layers.
[0052] In one embodiment, the composite electrospun membrane has an area of 0.5×0.5 m² and a thickness of 200±25 μm.
[0053] In one embodiment, the mass ratio of the glutaraldehyde to the water is 4 wt %.
[0054] In one embodiment, the cross-linking time of the composite electrospun membrane is 30 to 45 minutes, for example, 30 minutes.
[0055] In one embodiment, the cleaning is performed by placing in water.
[0056] In a certain embodiment, the drying is a drying method commonly used in the art, such as a vacuum drying method, and further, for example, vacuum drying at 60° C. for 24 hours.
[0057] In one embodiment, the method for preparing the fiber membrane comprises the following steps:
[0058] (1) electrospinning a polysaccharide solution to obtain an electrospun membrane; the polysaccharide solution comprises polysaccharide and an organic solvent; and salt is added during the electrospinning process;
[0059] (2) Based on the electrospun membrane 1, electrospinning a polysaccharide solution to obtain a composite electrospun membrane; the polysaccharide solution is composed of polysaccharide and an organic solvent; and no salt is added during the electrospinning;
[0060] (3) cross-linking the composite electrospun membrane obtained in step (2) with glutaraldehyde in water, washing, and drying to obtain a fiber membrane;
[0061] The fiber membrane is the fiber membrane mentioned above; the polysaccharide is 50kDa chitosan;
[0062] The organic solvent is trifluoroacetic anhydride;
[0063] The concentration of the polysaccharide solution is 5wt.%;
[0064] The electrospinning speed is 1 mL / h, where mL refers to the volume of the polysaccharide solution;
[0065] The negative voltage of the electrospinning is -3 kV;
[0066] The positive voltage of the electrospinning is 20 kV;
[0067] The electrospinning time of step (1) and step (2) is the same;
[0068] The salt is sodium chloride with an average particle size of 5000 nm;
[0069] In step (1), the rate of adding salt is 50 mg / min;
[0070] The rotation speed of the electrospinning support roller is 600 r / min;
[0071] The thickness of the composite electrospun membrane is 200±25 μm;
[0072] The mass ratio of the glutaraldehyde to the water is 4wt%;
[0073] The cleaning is placing in water;
[0074] The drying is vacuum drying at 60°C.
[0075] The present invention also provides a fiber membrane, which is prepared according to the above method.
[0076] The present invention also provides an application of the fiber membrane in preparing an antibacterial material or a bone tissue repair material, such as a periodontal defect repair material.
[0077] Compared with the prior art, the present invention has the following beneficial effects:
[0078] The present invention places polysaccharides into an organic solvent and stirs it with a magnetic stirrer to obtain a polysaccharide solution, then spins it into a film through electrostatic spinning technology, and obtains a finished repair film after cross-linking and curing with glutaraldehyde. The elasticity and mechanical properties of the hydrogel of the present invention are excellent, and it can be cut into various shapes according to needs; relative to traditional collagen products, the repair film of the present invention degrades slowly, which is beneficial to wound repair. At the same time, the repair film has good biological activity and biocompatibility, and has application value in promoting cell proliferation, antibacterial properties, and tissue defect repair. In addition, the preparation method of the present invention is simple and the raw materials are easily available. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 The cross-linked fiber membrane of Example 1;
[0080] Figure 2 is the fiber membrane before cross-linking of Example 1;
[0081] Figure 3 The electron microscope scanning images of the fiber membrane before cross-linking of Example 1 at different magnifications;
[0082] Figure 4 The electron microscope scanning images of the cross-linked fiber membrane of Example 1 at different magnifications;
[0083] Figure 5 The Escherichia coli inhibition zone performance of the fiber membrane of Example 1;
[0084] Figure 6 The Staphylococcus aureus inhibition zone performance of the fiber membrane of Example 1;
[0085] Figure 7 The co-culture antibacterial performance of the fiber membrane of Example 1;
[0086] Figure 8 is the cell compatibility of the fiber membrane in Example 1;
[0087] Fig. 9 The in vivo degradability of the fiber membrane of Example 1 after subcutaneous implantation for 14 days;
[0088] Fig.10 The in vitro osteogenic differentiation performance of the fiber membrane in Example 1. DETAILED DESCRIPTION
[0089] The technical scheme of the present invention is further described below in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources; the processes used, unless otherwise specified, all adopt conventional processes in the art.
[0090] Example 1
[0091] A nanofiber membrane for periodontal tissue repair, the preparation method of which is as follows:
[0092] (1) Chitosan with a molecular weight of 50 kDa and trifluoroacetic anhydride were prepared to obtain a polysaccharide solution containing 5 wt% chitosan.
[0093] (2) Put 10 ml of 5 wt.% polysaccharide solution into a syringe, slowly eject it through a syringe pump, and place it into an electrospinning instrument. The syringe pump propulsion speed is controlled at 1.0 ml / h, and the spinning time is 10 hours. The electrospinning instrument is a Shenzhen Tongli micro-nano electrospinning machine TL-BM-300. The electrospinning is controlled at a negative voltage of -3 kV and a positive voltage of 20 kV.
[0094] (3) In the first 5 hours of spinning (a total of 10 hours), sodium chloride with an average particle size of 50 μm was added at a rate of 50 mg / min to obtain an electrospun membrane containing sodium chloride; in the last 5 hours of spinning (a total of 10 hours), sodium chloride was no longer added, and the electrospun membrane containing sodium chloride was covered by spinning to obtain a double-layer electrospun membrane. The area of the electrospun membrane was 0.5*0.5 m² and the thickness was 200±25 μm.
[0095] (4) Place 200 mL of 4% glutaraldehyde aqueous solution at the bottom of a sealed box with a volume of about 10 L, place a bracket in the middle, and place the double-layer electrospun membrane obtained in step (3) in the 4% glutaraldehyde solution for cross-linking for 30 min. After taking it out, place it in distilled water for a period of time, and dry it in a vacuum drying oven at 60°C for 24 h to obtain a fiber membrane product 1 (the best ratio of the inner and outer layers is 1:1, the shape is block-shaped, the size is 0.5*0.5m², the structure is two layers, a dense layer and a loose layer, and the thickness is 200±25μm).
[0096] The pore size of the dense layer of the fiber membrane is 80±23μm, and the porosity of the loose layer is 12%.
[0097] Example 2
[0098] Referring to Example 1, the propulsion speed in step 2 is adjusted to 0.5 mL / h, the positive voltage is adjusted to 15 kV, and the cross-linking time in step 4 is adjusted to 45 min to obtain a fiber membrane product 2.
[0099] Example 3
[0100] Referring to Example 1, the concentration of the chitosan polysaccharide solution in step 1 is adjusted to 8 wt %, the propulsion speed in step 2 is adjusted to 0.5 mL / h, the positive voltage is adjusted to 15 kV, and the cross-linking time in step 4 is adjusted to 45 min to obtain a fiber membrane product 3.
[0101] Example 4
[0102] Referring to Example 1, the concentration of the chitosan polysaccharide solution in step 1 is adjusted to 3wt%, the propulsion speed in step 2 is adjusted to 0.5mL / h, the positive voltage is adjusted to 15kV, and the cross-linking time in step 4 is adjusted to 45min to obtain a fiber membrane product 4.
[0103] Structural characterization and performance testing:
[0104] (1) Appearance
[0105] The actual picture of the fiber membrane of Example 1 is as follows Figure 1 and Figure 2 As shown in Figure 2, it can be seen that the surface of the fiber membrane before cross-linking is relatively rough. Figure 2 As shown, the cross-linked film showed a smoother Figure 1 As shown, a portion of the image is reduced. Figure 1 The left picture shows the loose layer, and the right picture shows the dense layer. Figure 2 The left picture shows the loose layer, and the right picture shows the dense layer)
[0106] (2) Microstructure
[0107] The periodontal tissue repair nanofiber membrane of Example 1 before and after cross-linking was vacuum dried at 25°C and its morphology was tested by scanning electron microscopy. Figure 3 As shown, after cross-linking Figure 4 As shown. Figure 3 and Figure 4 It can be seen that the nanofiber membrane of Example 1 has different structural morphologies on both sides, one side is dense and the other side is loose ( Figure 3 The left picture shows the loose layer, and the right picture shows the dense layer. Figure 4 The left picture shows the loose layer, and the right picture shows the dense layer). After cross-linking, the loose layer shows porous characteristics, while the dense layer becomes more compact.
[0108] (3) Antibacterial properties
[0109] The periodontal tissue repair nanofiber membranes before and after cross-linking in Example 1 were respectively subjected to the inhibition zone method ( Figure 5 and Figure 6 ) and co-culture method ( Figure 7 ) was used to determine its inhibitory effect on Escherichia coli and Staphylococcus aureus. The culture medium used was LB culture medium. The results are as follows Figure 5 , Figure 6 and Figure 7 As shown; the paper was used as a blank control group, and the fiber membrane after cross-linking and the electrospun membrane before cross-linking were placed in culture dishes respectively. Figure 5 The inhibition zone method was used to determine the inhibitory effect of the fiber membrane on Escherichia coli. Figure 5 1 is the fiber membrane after cross-linking in Example 1; Figure 5 2 is the fiber membrane before cross-linking in Example 1; Figure 5 3 is a paper piece, and obvious inhibition zones appeared around 1 and 2. Figure 6 The inhibition zone method was used to determine the inhibitory effect of the fiber membrane on Staphylococcus aureus. Figure 6 1 is the fiber membrane before cross-linking in Example 1; Figure 6 2 is the fiber membrane after cross-linking in Example 1; Figure 6 3 is a paper piece, and obvious inhibition zones appeared around 1 and 2.
[0110] Figure 7 The co-culture method was used to determine the inhibitory effect of the fiber membrane on Escherichia coli and Staphylococcus aureus. The paper disc was used as the blank control group. 100 mg of the sample was added to 5 ml of 10 8 CFU / ml in a centrifuge tube, after culturing at 37°C for 24 hours, 100 μl of the bacterial solution in the centrifuge tube was collected and evenly coated on an LB agar plate, and then taken out and photographed after culturing at 37°C for 24 hours. The results show that the nanofiber membrane of Example 1 can significantly inhibit the growth of Escherichia coli and Staphylococcus aureus.
[0111] (4) Cell compatibility of materials
[0112] The periodontal tissue repair nanofiber membrane of Example 1 was placed in a 48-well plate, 100,000 fibroblasts (NIH 3T3 cell line, mainly fibroblasts) were implanted on the surface of each membrane and 0.5 mL of cell culture medium (DMEM medium containing 10% fetal bovine serum) was injected to culture the cells in a constant temperature incubator at 37°C, 99.9% humidity and 5 v / v% carbon dioxide. 5 µL of calcein and 5 µL of iodinated pyridinium were added to 5 mL of deionized sterile water and mixed, and allowed to stand for 10 minutes. 1 mL of each was added to a 96-well plate. Figure 8 As shown, compared with the blank group, there is no obvious difference in the living cells on the surface of the fiber membrane of Example 1, which indicates that the nanofiber membrane has excellent cell compatibility.
[0113] (5) Material degradability in vivo
[0114] The periodontal tissue repair nanofiber membrane of Example 1 was placed subcutaneously in mice (the mice were C57 mice, provided by Guangdong Medical Device Research Institute). The mice were killed on the 14th day, and the skin and subcutaneous tissue were cut open with ophthalmic scissors along the wound surface 1 cm, and placed in 4% paraformaldehyde for later use. Then, it was dehydrated, transparent, and wax-impregnated, and then embedded. After completion, H&E staining was performed to observe the cross-section tissue morphology. Fig. 9 As shown, the results showed that the nanofiber membrane did not undergo obvious degradation after 14 days in the body, and still maintained its supporting and protective effects. No adverse reactions such as calcification were found in the tissue, and it was not easy to cause rejection.
[0115] (6) Osteogenic differentiation performance
[0116] The periodontal tissue repair nanofiber membrane was placed in a 48-well plate, 100,000 rat bone marrow mesenchymal stem cells were implanted on the surface of each membrane, and 0.5 mL of cell culture medium (DMEM medium containing 10% fetal bovine serum) was injected. The cells were cultured in an incubator at 37°C, 99.9% humidity and 5v / v% carbon dioxide for 24 hours, and then taken out and photographed. Fig.10 As shown in the figure, after the membrane and bone marrow mesenchymal stem cells were co-cultured for 24 hours, many black spots (i.e., calcification spots) appeared on the surface. These spots were evenly distributed on the inner side of the membrane ( Fig.10 1 is the loose layer), but not on the outside ( Fig.10 2 is the dense layer), which indicates that the porous layer can accelerate osteogenic differentiation.
[0117] After testing, the performance of fiber membrane finished products 2~4 is similar to that of fiber membrane finished product 1.
[0118] The above embodiments are preferred implementation methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A fiber membrane, comprising a polysaccharide layer 1 and a polysaccharide layer 2, wherein the polysaccharide layer 1 covers the polysaccharide layer 2, the material of the polysaccharide layer 1 is a cross-linked polysaccharide, the material of the polysaccharide layer 2 is a cross-linked polysaccharide, and the pores of the polysaccharide layer 1 are larger than the pores of the polysaccharide layer 2.
2. The fiber membrane according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The fiber membrane area is 0.5×0.5㎡; (2) The thickness of the fiber membrane is 200±25 μm; (3) The fiber membrane consists of a first polysaccharide layer and a second polysaccharide layer; (4) The number of layers of the polysaccharide layer 1 is 1; (5) The number of layers of the polysaccharide layer 2 is 1; (6) The pore size of the polysaccharide layer 1 is 80±23 μm; (7) The porosity of the second polysaccharide layer is 10% to 14%; (8) In the polysaccharide layer, the cross-linking is performed by glutaraldehyde cross-linking; (9) In the second polysaccharide layer, the cross-linking is performed by glutaraldehyde cross-linking; (10) In the first polysaccharide layer, the polysaccharide is one of chitosan, cellulose, starch, alginate and dextran; (11) In the second polysaccharide layer, the polysaccharide is one of chitosan, cellulose, starch, alginate and dextran; (12) The fiber membrane is used as an antibacterial material and / or a bone tissue repair material; (13) The polysaccharide layer 1 and the polysaccharide layer 2 are bonded together.
3. The fiber membrane according to claim 2, characterized in that: It meets one or more of the following conditions: (1) The porosity of the polysaccharide layer 2 is 12%; (2) In the polysaccharide layer 1, the polysaccharide is chitosan, such as 50 kDa chitosan; (3) In the second polysaccharide layer, the polysaccharide is chitosan, such as 50 kDa chitosan; (4) The fiber membrane is used as a periodontal defect repair material.
4. The fiber membrane according to claim 1, characterized in that: It meets the following conditions: (1) The thickness of the fiber membrane is 200±25 μm; (2) The fiber membrane consists of a first polysaccharide layer and a second polysaccharide layer; (3) The polysaccharide layer 1 is bonded to the polysaccharide layer 2; (4) The material of the polysaccharide layer 1 is a cross-linked polysaccharide; (5) The material of the polysaccharide layer 2 is a cross-linked polysaccharide; (6) The number of layers of the polysaccharide layer 1 is 1; (7) The number of layers of the polysaccharide layer 2 is 1; (8) The pore size of the polysaccharide layer 1 is 80±23 μm; (9) The porosity of the second polysaccharide layer is 12%; (10) The cross-linking is carried out by glutaraldehyde cross-linking; (11) In the first polysaccharide layer, the polysaccharide is 50 kDa chitosan; (12) In the second polysaccharide layer, the polysaccharide is 50 kDa chitosan; (13) The fiber membrane is used as a periodontal defect repair material.
5. A method for preparing a fiber membrane, comprising the following steps: (1) electrospinning a polysaccharide solution to obtain an electrospun membrane; the polysaccharide solution comprises polysaccharide and an organic solvent; and salt is added during the electrospinning process; (2) Based on the electrospun membrane 1, the polysaccharide solution is electrospun to obtain a composite electrospun membrane; The polysaccharide solution consists of polysaccharide and organic solvent; in the electrospinning, no salt is added; (3) Cross-linking the composite electrospun membrane obtained in step (2) with glutaraldehyde in water, washing, and drying to obtain a fiber membrane.
6. The method for preparing a fiber membrane according to claim 5, characterized in that: It meets one or more of the following conditions: (1) The fiber membrane is the fiber membrane according to any one of claims 1 to 4; (2) The manufacturer of the electrospinning equipment is Shenzhen Tongli Micro-Nano; (3) The polysaccharide is one of chitosan, cellulose, starch, alginate and dextran; (4) The organic solvent is a volatile electrospinning solution; (5) The concentration of the polysaccharide solution is 3.0-8.0 wt.%; (6) The electrospinning speed is 0.5-1 mL / h; mL refers to the volume of the polysaccharide solution; (7) The negative voltage of the electrospinning is -3 kV; the positive voltage of the electrospinning is 15-20 kV; (8) The electrospinning time in step (1) is the same as the electrospinning time in step (2); (9) In step (1), the electrospinning time is 4-6 hours; in step (2), the electrospinning time is 4-6 hours; (10) The salt is sodium chloride, potassium chloride, copper sulfate, sodium bicarbonate and calcium chloride; the average particle size of the salt is 1 to 10 μm; (11) The salt addition rate is 50 mg / min; (12) The speed of the electrospinning roller should be controlled at 200-2000 r / min; (13) The composite electrospun membrane has two layers; (14) The mass ratio of the glutaraldehyde to the water is 4wt%; (15) The cross-linking time of the composite electrospun membrane is 30 to 45 minutes; (16) The cleaning is performed by placing the device in water; (17) The drying method is a vacuum drying method.
7. The method for preparing a fiber membrane according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The polysaccharide is chitosan, such as 50 kDa chitosan; (2) The organic solvent is one of methanol, hexafluoroisopropanol, acetone, trifluoroacetic anhydride and water, such as trifluoroacetic anhydride; (3) The concentration of the polysaccharide solution is 5wt.%; (4) The electrospinning speed is 1 mL / h; mL refers to the volume of the polysaccharide solution; (5) The positive voltage of the electrospinning is 20 kV; (6) In step (1), the electrospinning time is 5 h; in step (2), the electrospinning time is 5 h; (7) The salt is sodium chloride; the average particle size of the salt is 5 μm; (8) The speed of the electrospinning support roller should be controlled at 500-8000 r / min, for example, 600 r / min; (9) The cross-linking time of the composite electrospun membrane is 30 min; (10) The drying method is vacuum drying at 60°C for 24 hours.
8. The method for preparing a fiber membrane according to claim 5, characterized in that: It meets the following conditions: (1) The fiber membrane is the fiber membrane according to any one of claims 1 to 4; (2) The polysaccharide is 50 kDa chitosan; (3) The organic solvent is trifluoroacetic anhydride; (4) The concentration of the polysaccharide solution is 5wt.%; (5) The electrospinning speed is 1 mL / h, where mL refers to the volume of the polysaccharide solution; (6) The negative voltage of the electrospinning is -3 kV; the positive voltage of the electrospinning is 20 kV; (7) The electrospinning time in step (1) is the same as the electrospinning time in step (2); (8) The salt is sodium chloride with an average particle size of 5000 nm; (9) The salt addition rate is 50 mg / min; (10) The speed of the electrospinning roller should be controlled at 600 r / min; (11) The composite electrospun membrane has an area of 0.5×0.5 m² and a thickness of 200±25 μm; (12) The mass ratio of the glutaraldehyde to the water is 4wt%; (13) The cleaning is performed by placing the device in water; (14) The drying method is vacuum drying at 60°C.
9. A fiber membrane prepared according to the method of any one of claims 5-8.
10. Use of the fiber membrane according to any one of claims 1 to 4 and 9 in the preparation of antibacterial materials and / or bone tissue repair materials, such as periodontal defect repair materials.
Citation Information
Patent Citations
Single-layer and double-layer polycaprolactone-based guided tissue regeneration membranes and preparation method thereof
CN103736153A
Preparation method and application of layered Steiner network structure fiber membrane
CN111220606A
Double-layer guided tissue regeneration membrane and preparation method thereof
CN112553785A
Double-layer polyurethane film, preparation method thereof and application of double-layer polyurethane film as oral soft tissue repair film
CN118846260A
Periodontal disease treatment material
JP2010284220A
Cited By
Double-layer tissue engineering drug-loaded stent as well as preparation method and application thereof
CN120393125A